The Implementation of Ice Breakers Toward Improvement Students' Motivation in Learning English at Software Engineering in SMK TI Garuda Nusantara Cimahi - Annisa Annisa; Trisnendri Syahrizal (IKIP Siliwangi, 2019)
The purpose of this study is to find out the improvement students’ motivation using ice breaker in learning English at the tenth grade of software engineering major in SMK TI Garuda Nusantara Cimahi. The data obtained from the result of observation and students learning outcomes from the test (pretest and posttest). The result showed Students who were completed value with KKM > 70 in the pre-cycle has 28.60% and in the first cycle increased to 67.80% than in the second cycle improved to 100%. The average student learning outcomes in the first cycle amounted to 66.29 and the second cycle increased to 73.09 so the average student learning outcomes from cycle I to cycle II increased by 6.8. It means there was an improvement in students’ motivation after carried out classroom actions research. Based on the fact, the researcher concluded that the ice breaker was effective to improve students’ motivation in learning English at the tenth grade of office software engineering major in SMK TI Garuda Nusantara Cimahi. It was also proved by observation students when teaching-learning in the classroom. Students feel enjoy, be active, feeling happiness, focus on material and stay in the classroom during the learning process.Keywords: Teaching Method, Motivation, Ice breaker, learning process